Enhancing student literacy and creativity through collaborative literary mentoring programs - Nofvia De Vega; Syarifa Rafiqa (Journal of Community Service and Empowerment, 2025)
Vocational high school students' literacy and creativity levels still need to be optimized through innovative and collaborative learning activities. This program aims to improve these competencies through the development of literary works based on mentoring and collaboration between lecturers, teachers, and students. This program is held at SMKN 1 Tanjung Palas Timur and focuses on literary works development as a tool to improve students' literacy and creativity through community service programs. The program involved a hands-on, participatory framework that engaged students in active learning and collaborative experiences. Results from pre-test and post-test quantitative data showed improved student writing ability. Students’ creativity scores went from an average of 55 to 85, while structure scores increased from 60 to 80. The language use rose from 50 to 80, the emotional expression from 55 to 90, the theme depth from 60 to 85, and the readability from 65 to 90. In addition, these findings validate previous outcomes of mentoring on student literacy skills and students’ confidence in creative writing. Finally, the study results indicate that analogous efforts may be helpful in other classroom settings to support students in establishing literacy and creativity.